Teachers' characteristics predict students' guidance for healthy lifestyle: a cross-sectional study in Arab-speaking schools - Rachel Wilf-Miron; Roaa Kittany; Mor Saban; Ilya Kagan; Mor Saban (BMC, 2022)
Highlights Teachers' health behaviors may affect their position as role models for students. Israeli Arab teachers had unfavorable health behaviors and high body mass index. Burnout inversely correlated with organizational commitment and job satisfaction. Better perceived health predicted lower burnout and higher job satisfaction. Improved school environment could improve teachers' wellbeing and role modeling.